Моделювання задачами оптимізації з дробово-лінійною цільовою функцією на поліпереставленнях - Ємець, О.; Романова, Н.; Yemets’, O.; Romanova, N. (Видавництво Національного університету “Львівська політехніка”, 2005)
Побудовано математичну модель оптимізаційної задачі з дробово-лінійною цільовою функцією. Обгрунтовано використання множини поліпереставлень як апарат математичного моделювання задачами оптимізації з дробово-лінійними цільовими функціями.

The mathematical model of the optimization problem with fractionally linear criterion function is designed. The possibility to use a great number of poly per mutations as an apparatus of mathematical simulation with optimization problems the fractionally linear criterion function is explained.
Simulation with the help of the optimization problem on the polypermutations with the fractionally linear criterion function
Keywords: математична модель; поліпереставлення; дробово-лінійна цільова функція; mathematical model; polypermutations; fractionally linear criterion function; 519.85